Answer:
![x = 0, -\frac{5}{2}](https://tex.z-dn.net/?f=x%20%3D%200%2C%20-%5Cfrac%7B5%7D%7B2%7D)
Step-by-step explanation:
First move all terms to one side of the equation to set them equal to 0
That is already done in your problem
The try to factor, if possible. In your case, factor out x
x(2x + 5) = 0 Now, use the property that says if AB = 0, then A = 0 or B = 0 or both A and B equal 0
So, x = 0 or 2x + 5 = 0
2x = -5
x = ![-\frac{5}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B2%7D)
Always check your results in the original equation to see if they work
![2(0^{2} + 5(0) = 0 + 0 = 0\\](https://tex.z-dn.net/?f=2%280%5E%7B2%7D%20%20%2B%205%280%29%20%3D%200%20%2B%200%20%3D%200%5C%5C)
and ![2(-\frac{5}{2} )^{2} + 5(-\frac{5}{2} )\\ = 2(\frac{25}{4} ) - \frac{25}{2} \\ = \frac{25}{2} - \frac{25}{2} = 0](https://tex.z-dn.net/?f=2%28-%5Cfrac%7B5%7D%7B2%7D%20%29%5E%7B2%7D%20%20%2B%205%28-%5Cfrac%7B5%7D%7B2%7D%20%29%5C%5C%20%3D%202%28%5Cfrac%7B25%7D%7B4%7D%20%29%20-%20%20%5Cfrac%7B25%7D%7B2%7D%20%20%5C%5C%20%3D%20%20%5Cfrac%7B25%7D%7B2%7D%20%20-%20%20%5Cfrac%7B25%7D%7B2%7D%20%3D%200)
Both results make the equation true, so ![x = 0, -\frac{5}{2}](https://tex.z-dn.net/?f=x%20%3D%200%2C%20-%5Cfrac%7B5%7D%7B2%7D)